Global agenda for social justice 2. (SSSP Agendas for Social Justice Ser., 2022)
The Global Agenda for Social Justice provides accessible insights into some of the world's most pressing social problems and proposes practicable international public policy responses to those problems. Written by a highly respected team of authors brought together by the Society for the Study of Social Problems (SSSP), chapters examine topics such as education, violence, discrimination, substance abuse, public health, and environment. The volume provides recommendations for action by governing officials, policy makers, and the public around key issues of social justice. The book will be of interest to scholars, practitioners, advocates, journalists, and students interested in public sociology, the study of social problems, and the pursuit of social justice.